Effects of electrical stimulation with alternating fields on the osseointegration of titanium implants in the rabbit tibia - a pilot study - Klinder, A.; Möws, F.; Ziebart, J.; Su, Y.; Gabler, C.; Jonitz-Heincke, A.; van Rienen, U.; Ellenrieder, M.; Bader, R. (Frontiers in Bioengineering and Biotechnology, 2024)
Electrical stimulation has been used as a promising approach in bone repair for several decades. However, the therapeutic use is hampered by inconsistent results due to a lack of standardized application protocols. Recently, electrical stimulation has been considered for the improvement of the osseointegration of dental and endoprosthetic implants. In a pilot study, the suitability of a specifically developed device for electrical stimulation in situ was assessed. Here, the impact of alternating electric fields on implant osseointegration was tested in a gap model using New Zealand White Rabbits. Stimulation parameters were transmitted to the device via a radio transceiver, thus allowing for real-time monitoring and, if required, variations of stimulation parameters. The effect of electrical stimulation on implant osseointegration was quantified by the bone-implant contact (BIC) assessed by histomorphometric (2D) and µCT (3D) analysis. Direct stimulation with an alternating electric potential of 150 mV and 20 Hz for three times a day (45 minutes per unit) resulted in improved osseointegration of the triangular titanium implants in the tibiae of the rabbits. The ratio of bone area in histomorphometry (2D analysis) and bone volume (3D analysis) around the implant were significantly increased after stimulation compared to the untreated controls at sacrifice 84 days after implantation. The developed experimental design of an electrical stimulation system, which was directly located in the defect zone of rabbit tibiae, provided feedback regarding the integrity of the stimulation device throughout an experiment and would allow variations in the stimulation parameters in future studies. Within this study, electrical stimulation resulted in enhanced implant osseointegration. However, direct electrical stimulation of bone tissue requires the definition of dose-response curves and optimal duration of treatment, which should be the subject of subsequent studies.